2012
DOI: 10.1177/0883073812457462
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Self-Report Health-Related Quality of Life Measures in Young Patients With Tourette Syndrome

Abstract: Tourette syndrome is a neurodevelopmental disorder characterized by tics and comorbid behavioral problems. This study compared child- and parent-reported quality of life and everyday functioning. We assessed 75 children with Tourette syndrome, of which 42 (56%) had comorbid conditions (obsessive-compulsive disorder = 25; attention-deficit hyperactivity disorder = 6; both comorbidities = 4). All patients completed psychometric instruments, including the Gilles de la Tourette Syndrome–Quality of Life Scale for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 16 publications
3
30
1
2
Order By: Relevance
“…The moderate parent–child correlations are also consistent with findings of moderate correlations between parent and child ratings on functional impairment or quality of life . Children in several other studies of Tourette syndrome also appear to have reduced quality of life and worse function . A study using the Gilles de la Tourette Syndrome‐Quality of Life Scale for Children and Adolescents (child report) and the CTIM‐P found that parents placed more emphasis on comorbid conditions, while children more readily noticed the impact of tics.…”
Section: Discussionmentioning
confidence: 99%
“…The moderate parent–child correlations are also consistent with findings of moderate correlations between parent and child ratings on functional impairment or quality of life . Children in several other studies of Tourette syndrome also appear to have reduced quality of life and worse function . A study using the Gilles de la Tourette Syndrome‐Quality of Life Scale for Children and Adolescents (child report) and the CTIM‐P found that parents placed more emphasis on comorbid conditions, while children more readily noticed the impact of tics.…”
Section: Discussionmentioning
confidence: 99%
“…Differences have been found between child and parent reports of health‐related quality of life in Tourette syndrome, potentially influenced by parental feelings of anxiety and responsibility (Cavanna et al . ), and qualitative evidence has suggested that some children experience their parents to be more worried about the tics than they are (Rivera‐Navarro et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of providing a reflective space for parents to discuss their worries, thoughts and feelings was also endorsed across all factors. Differences have been found between child and parent reports of health-related quality of life in Tourette syndrome, potentially influenced by parental feelings of anxiety and responsibility (Cavanna et al 2013d), and qualitative evidence has suggested that some children experience their parents to be more worried about the tics than they are (Rivera-Navarro et al 2013). Space to discuss parents' worries is thus a fundamental component of interventions, and stress management Parenting interventions in tic disorders: parents' perspectives 393 and coping strategies may also reduce potentially detrimental effect of parents' concerns on their children.…”
Section: Discussionmentioning
confidence: 99%
“…There are major management and prognostic implications to having a dual diagnosis; Robertson (2006a) reviewed the treatment of both conditions and suggested that the most problematic symptoms should be addressed and treated first (Rizzo et al, 2013;Robertson, 2006a). In order to achieve the most effective management strategies for children, it is important that the assessment incorporates feedback from teachers, parents, or other relatives, whenever possible (Termine et al, 2011;Cavanna, Luoni, et al, 2012). While pharmacological therapies such as the two alpha-2 agonists clonidine and guanfacine have proven effective for both tics and ADHD symptoms (Eddy, Rickards, & Cavanna, 2011;Robertson, 2006a), the use of central nervous stimulants first line for ADHD can precipitate tics.…”
Section: Comorbidities: Attention-deficit and Hyperactivity Disordermentioning
confidence: 99%